Identifying a Minor Histocompatibility Antigen in Mauritian Cynomolgus Macaques Encoded by APOBEC3C - Weinfurter, Jason T.; Graham, Michael E.; Ericsen, Adam J.; Matschke, Lea M.; Llewellyn-Lacey, Sian; Price, David A.; Wiseman, Roger W.; Reynolds, Matthew R. (Frontiers in Immunology, 2020)
Allogeneic hematopoietic stem cell transplants can lead to dramatic reductions in human immunodeficiency virus (HIV) reservoirs. This effect is partially mediated by donor T cells recognizing lymphocyte-expressed minor histocompatibility antigens (mHAgs). The potential to mark malignant and latently infected cells for destruction makes mHAgs attractive targets for cellular immunotherapies. However, testing such HIV reservoir reduction strategies will likely require preclinical studies in nonhuman primates (NHPs). In this study, we used a combination of alloimmunization, whole exome sequencing, and bioinformatics to identify a mHAg in Mauritian cynomolgus macaques (MCMs). We mapped the minimal optimal epitope to a 10-mer peptide (SW10) in apolipoprotein B mRNA editing enzyme catalytic polypeptide-like 3C (APOBEC3) and determined the major histocompatibility complex class I restriction element as Mafa-A1*063, which is expressed in almost 90% of MCMs. APOBEC3C SW10-specific CD8+ T cells recognized immortalized B cells but not fibroblasts from a mHAg positive MCM. These results provide a framework for identifying mHAgs in a nontransplant setting and suggest that APOBEC3C SW10 may be a model antigen in NHPs to test mHAg-targeted immunotherapies.